تقويم الانسان فى القرآن الكريم - حمو، عبدالمحسن قاسم الحاج (جامعة الموصل - كلية التربية الأساسية, 2008)
الحمد لله رب العالمين والصلاة والسلام على اشرف المرسلين سيدنا محمد وعلى آله وصحبه أجمعين وبعد: فقد اخترت الكتابة في هذا الموضوع لما ق أ رته من فضائل القرآن والتمسك به والتأدب بأدبه ولأنه جماع الخير، وقد سئلت ام المؤمنين السيدة عائشة (رضي الله عنها) عن خلقه (صلى الله عليه وسلم) فقالت: (كان خلقه القرآن) ففي القرآن الكريم علم ما ينبغي ان يكون عليه الإنسان من الخلال الطيبة والسجايا النبيلة وما ينبغي ان يتجنبه من العادات الرديئة والصفات المشينة لإنشاء مجتمع مثالي واقعي. فالإسلام يريد من المسلم ان يكون قرآناً يمشي على الارض بقدميه وينظر بعينيه ويتكلم بشفتيه ونبراسه قوله تعالى: (إن هذا القرآن يهدي للتي هي أقوم ويبشر المؤمنين الذين يعملون الصالحات أن لهم أجراً كبيراً) فمن أراد العلم فعليه بالقرآن. ومن أراد الهداية فعليه بالقرآن، ومن اراد الحكمة والسياسة فعليه بالقرآن فانه قد جمع ثمار الكتب السابقة. Praise be to Allah Who Descended the Holly book onto the world to be a Warner to the whole world, and peace be upon his messenger Mohammed who calls the people for Allah worship and became the guiding light and may Allah be pleased with all his companions and every man who followed their track till the judgment day. I have chosen this subject because holding onto the Quran is a great thing and that we should follow the Quran and its disciplines because it includes all the good Allah created. Aisha (prophet Mohammed's wife, may Allah be pleased with her) was asked once about the manners of the prophet and she said: "His manner was the Quran. "The Noble Quran teaches how should man be and the good and noble qualifications he should have and the bad qualifications man should abandons to create an ideal society. Islam encourages each of its followers to be as a Quran that looks with two eyes, speaks with lips and walk with feet following what Almighty Allah says: "Verily, this Quran guides unto that which is the straightest, and gives tidings to the believers who do good works that theirs will be a great reward" So everyone who seeks knowledge should learn the Noble Quran in the first place, and anyone who seeks guidance, politics and wisdom should learn Quran.
642684
Keywords: الآداب الاسلامية -- القرآن الكريم -- الاخلاق الاسلامية -- القيم الاخلاقية -- الانسان -- السلوك -- المجتمع الاسلامى